Intraoral findings in patients in a Colombian population infected with SARS-CoV-2: series of cases - Vásquez Viana, Maria Jose (2022)
Objective. To identify and describe the oral lesions found in patients with SARS-CoV-2 infection. Methods. Series of cases with description of 11 patients with SARS-CoV-2 infection confirmed by nasopharyngeal swab or serological test to confirm the infection; with the presence of intraoral manifestations of different types. All patients underwent tele-consultation by a stomatologist and relevant data such as age, sex, history of pre-existing diseases, type of stomatological lesion present, site and symptomatology, among others, were collected. All patients signed an informed consent form. Results. Of the 11 positive cases for SARS-CoV-2, 63.63% (n=7) of the patients were female and 36.36% (n=4) were male. All patients (100%) were diagnosed by molecular and serological tests, 90.90% were diagnosed by viral PCR and 9.09% were diagnosed by antigen test. Ulcerative lesions predominated in 54.54%; followed by pseudoplaque and erythema in 18.18% of patients, respectively. Vesicles and crusts were present in 9.09% respectively. Ageusia and anosmia were present in 72.72 (n=8), and 45.45% (n=5) of patients showed comorbidities such as diabetes, arterial hypertension and hypothyroidism. Conclusions. This viral disease presents with oral lesions and it is usually the first and even the only manifestation during its course. That is why it is important to take into account and identify these lesions, and know their relationship with the therapeutic management, immunological compromise or the disease itself.